2010
DOI: 10.3928/1081597x-20090910-02
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking for Ectasia After Excimer Laser Refractive Surgery: 1-Year Results

Abstract: One year after surgery, CXL appears to stabilize eyes with ectasia consequent to excimer laser refractive surgery and improve BSCVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 35 publications
7
67
1
3
Order By: Relevance
“…Several small, prospective clinical studies have evaluated CXL for PLE and found that visual acuity and keratometric measures either significantly stabilized or improved. All those studies had only 1 year of follow-up [144,145,146,147]. A retrospective study evaluated 26 eyes with PLE (23 eyes) and with ectasia after PRK (3 eyes) during a 2-year follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Several small, prospective clinical studies have evaluated CXL for PLE and found that visual acuity and keratometric measures either significantly stabilized or improved. All those studies had only 1 year of follow-up [144,145,146,147]. A retrospective study evaluated 26 eyes with PLE (23 eyes) and with ectasia after PRK (3 eyes) during a 2-year follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…In the entire study group, the improvements in CDVA and maximum keratometry after CXL treatment were in agreement with the previous studies. 9,10,[18][19][20] In the current literature, a small number of studies investigated the effects of preoperative patient characteristics on outcomes of CXL treatment. Koller et al 21 evaluated the effects of maximum K, preoperative CDVA, and age on complication and failure rates of CXL treatment for primary keratectasia.…”
Section: Eyementioning
confidence: 99%
“…As for the treatment of ectasia after LASIK, Hafezi et al [3 ]reported a series of 10 eyes with 25 months of follow-up in which there was a reduction in Kmax at 12 months in all cases and an improvement of CDVA in 40% of the cases. Good results were also observed by Vinciguerra et al [14]. However, the role of CXL alone in improving the visual function was limited while the effectiveness of halting the progression process has been demonstrated.…”
Section: Discussionmentioning
confidence: 73%